2002
DOI: 10.1073/pnas.162077099
|View full text |Cite
|
Sign up to set email alerts
|

Dimerization of cotton fiber cellulose synthase catalytic subunits occurs via oxidation of the zinc-binding domains

Abstract: Cellulose synthase (CesA) proteins are components of CesA complexes (rosettes) and are thought to catalyze the chain elongation step in glucan polymerization. Little is understood about rosette assembly, including how CesAs interact with each other or with other components within the complexes. The first conserved region at the N terminus of plant CesA proteins contains two putative zinc fingers that show high homology to the RING-finger motif. We show that this domain in GhCesA1 can bind two atoms of Zn 2؉ , … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
172
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(177 citation statements)
references
References 36 publications
5
172
0
Order By: Relevance
“…Our results demonstrated that AtCESA2 could homodimerize and that the zinc finger domain of AtCESA2 was important for the interaction (Fig. 8B), consistent with previously reported results (Kurek et al, 2002). In contrast, no E3 ligase activity was detected in the in vitro assay for detecting the E3 ligase activity of RING finger proteins (data not shown).…”
Section: Atcesa2 Interacts With Itself Through the N-terminal Zinc-bisupporting
confidence: 93%
See 2 more Smart Citations
“…Our results demonstrated that AtCESA2 could homodimerize and that the zinc finger domain of AtCESA2 was important for the interaction (Fig. 8B), consistent with previously reported results (Kurek et al, 2002). In contrast, no E3 ligase activity was detected in the in vitro assay for detecting the E3 ligase activity of RING finger proteins (data not shown).…”
Section: Atcesa2 Interacts With Itself Through the N-terminal Zinc-bisupporting
confidence: 93%
“…8A). Kurek et al (2002) confirmed that GhCESA1 could form homodimers as well as heterodimers with GhCESA2 through the zinc-binding domain. To investigate whether AtCESA2 can homodimerize and to identify the domain responsible, we performed a yeast (Saccharomyces cerevisiae) two-hybrid assay with different truncations of AtCESA2 protein.…”
Section: Atcesa2 Interacts With Itself Through the N-terminal Zinc-bimentioning
confidence: 58%
See 1 more Smart Citation
“…Tests of protein-protein interactions in the yeast (Saccharomyces cerevisiae) two-hybrid system did not reveal any interactions between the second cytoplasmic domains of CesA proteins, and the second cytoplasmic domains did not show any interactions with the first cytoplasmic domains (data not shown). The first cytoplasmic domains of CesA proteins have been shown recently to interact with each other and are proposed to mediate the formation of the rosette complexes (Kurek et al, 2002). Our data suggest that the second cytoplamsic domains of AtCesA proteins might not be involved in direct interactions between CesA polypeptides; rather, they might mediate interactions of CesA proteins with other cellular components in the rosette complex.…”
Section: Possible Mechanisms For the Dominant Negative Effect Of The mentioning
confidence: 65%
“…The exact biochemical activity of each CesA isoform, although speculated upon (Read and Bacic 2002), has not yet been shown experimentally apart from one instance in which yeastexpressed GhCesA1 was able to convert sitosterol-b-glucoside to sitosterol cellodextrins, thus confirming their ability to synthesise (1,4)-b-glucan linkages (Peng et al 2002). The CesA isoforms interact directly and when all three are present, they form higher order oligomeric structures involving homodimers (Kurek et al 2002;Gardiner et al 2003;Atanassov et al 2009). Through the use of tagged CesA proteins, it may now be possible to purify CSCs from detergent-soluble extracts and establish whether any other proteins are permanent components of the complex.…”
Section: Cellulosementioning
confidence: 97%